Visualization of Forest Education Using CiteSpace: A Bibliometric Analysis - Sun, Yifan; Li, Linfeng; Yang, Qingting; Zong, Bobo (Forests, 2025)
In recent years, forest education has become a critical element in global environmental governance. This study employed the CiteSpace tool to systematically analyze 2917 titles of the forest education literature from the Web of Science Core Collection. The goal was to explore the spatial and temporal trends, thematic evolution, and emerging research directions in this field. The research shows that in recent years, the annual number of published papers on forest education has been on a continuous upward trend, and the attention to the subject has increased significantly. The research field mainly takes the United States in North America as the core center, with the joint participation of scholars from Europe and Asia. The development trajectory of the discipline shows a trend of gradual expansion toward multidisciplinary intersections and multidisciplinary integration based on traditional forestry and environmental sciences. Research hotspots mainly focus on core issues such as forest management, climate change, ecosystem services, and biodiversity. In recent years, they have expanded to include willingness to pay, prevalence, and student groups. It is expected that the research focus in the coming years will be on the cross-cutting issues of integrating forests with the economy, social public health, environmental protection, and sustainable development.